Role of MAPT mutations and haplotype in frontotemporal lobar degeneration in Northern Finland - Tuominen Hannu; Kuivaniemi Katja; Krüger Johanna; Kaivorinne Anna-Lotta; Moilanen Virpi; Majamaa Kari; Remes Anne M (BMC Neurology, 2008)
Abstract Background Frontotemporal lobar degeneration (FTLD) consists of a clinically and neuropathologically heterogeneous group of syndromes affecting the frontal and temporal lobes of the brain. Mutations in microtubule-associated protein tau ( MAPT ), progranulin ( PGRN ) and charged multi-vesicular body protein 2B ( CHMP2B ) are associated with familial forms of the disease. The prevalence of these mutations varies between populations. The H1 haplotype of MAPT has been found to be closely associated with tauopathies and with sporadic FTLD. Our aim was to investigate MAPT mutations and haplotype frequencies in a clinical series of patients with FTLD in Northern Finland. Methods MAPT exons 1, 2 and 9–13 were sequenced in 59 patients with FTLD, and MAPT haplotypes were analysed in these patients, 122 patients with early onset Alzheimer's disease (eoAD) and 198 healthy controls. Results No pathogenic mutations were found. The H2 allele frequency was 11.0% ( P = 0.028) in the FTLD patients, 9.8% ( P = 0.029) in the eoAD patients and 5.3% in the controls. The H2 allele was especially clustered in patients with a positive family history ( P = 0.011) but did not lower the age at onset of the disease. The ApoE4 allele frequency was significantly increased in the patients with eoAD and in those with FTLD. Conclusion We conclude that although pathogenic MAPT mutations are rare in Northern Finland, the MAPT H2 allele may be associated with increased risks of FTLD and eoAD in the Finnish population.